Septorhinoplasty and Its Relevance to Health Outcomes: Functional and Psychosocial Assessment - Topuria, Mariam (European Scientific Journal, ESJ, 2026)
Background: Septorhinoplasty aims to address both aesthetic and functional nasal concerns, and its impact may extend across multiple dimensions of daily living. This study evaluated the functional, psychosocial, and quality-of-life effects of septorhinoplasty using validated patient-reported outcome measures. Methods: A prospective single-centre cohort design was employed. Descriptive statistics (means and standard deviations) were calculated. The Wilcoxon matched-pairs test was used to assess the differences between pre- and postoperative outcomes, and the Spearman rank correlation test evaluated the associations between functional improvement and psychosocial outcomes. A priori sample size estimation supported adequate statistical power (power >95%, α <0.05). A total of 150 patients completed the NOSE questionnaire, the Stress Assessment Questionnaire, and the WHOQOL-BREF preoperatively and at the six-month follow-up. Statistical analyses were performed using SPSS software. Results: Postoperative evaluations demonstrated clinically and statistically significant improvements in nasal function (NOSE scores, p<0.001). Psychological outcomes showed notable enhancements in self-esteem and reductions in stress-related symptoms (Z=8.44, p<0.001). WHOQOL-BREF revealed significant gains in physical, psychological, and social domains (all p<0.001). Greater functional improvement was moderately associated with better psychological and social outcomes (r=0.5, p<0.05). Conclusion: Septorhinoplasty significantly improves not only nasal airflow and facial satisfaction but also multiple dimensions of health-related quality of life, including sleep, energy, social confidence, and psychological well-being. Although limited by its single-centre design and absence of long-term follow-up, these findings highlight the broader functional and psychosocial relevance of septorhinoplasty beyond cosmetic correction.